Knowledge of and attitudes to Occupational Health & Safety among tutors of a Vocational Training Institute (IIEK) in Greece: A pilot study. - Stavroula Bibila (Occupational Health and Safety Society of Nepal, 2012)
This study aimed to develop two instruments, one for measuring knowledge of Occupational Health & Safety (OHS) and one for measuring attitudes to OHS, to examine differences in knowledge and attitudes among tutors teaching at a private vocational training institute in Greece (IIEK) and to identify significant predictors of OHS knowledge. For the 9-item knowledge scale developed, a K-R 20 of 0.60 was generated while for the 9-item attitude scale a Cronbach's alpha (α) of 0.71 was generated. A cross-sectional, comparative research design was followed and the population (N=71) was stratified into "vocational area of expertise" groups. A proportional stratified random sampling strategy was used.   It was found that, for the sampled tutors (n=31), "hours of OHS training" was the sole significant predictor of OHS knowledge contributing for 76% of the explained variance.  No significant contributions to OHS knowledge were made by "vocational area of expertise", "years of teaching experience" and "attitudes to OHS".  DOI: http://dx.doi.org/10.3126/ijosh.v2i1.5341 International Journal of Occupational Safety and Health, Vol. 2 No. 1 (2012) 15-25